2013
DOI: 10.1152/ajpendo.00651.2012
|View full text |Cite
|
Sign up to set email alerts
|

Lack of myostatin impairs mechanical performance and ATP cost of contraction in exercising mouse gastrocnemius muscle in vivo

Abstract: Although it is well established that the lack of myostatin (Mstn) promotes skeletal muscle hypertrophy, the corresponding changes regarding force generation have been studied mainly in vitro and remain conflicting. Furthermore, the metabolic underpinnings of these changes are very poorly documented. To clarify this issue, we have investigated strictly noninvasively in vivo the impact of the lack of Mstn on gastrocnemius muscle function and energetics in Mstn-targeted knockout (Mstn Ϫ/Ϫ ) mice using 1 H-magneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 36 publications
3
22
0
Order By: Relevance
“…Actually, we showed that muscle hypertrophy was not accompanied by a proportional increase in absolute force. On the contrary, specific force was reduced in animals treated with sActRIIB-Fc, in agreement with what has been already reported in hypertrophied muscle of myostatin-deficient mice (2,19,42). Third, we observed that sActRIIB-Fc treatment did not improve maximal tetanic force in vivo.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Actually, we showed that muscle hypertrophy was not accompanied by a proportional increase in absolute force. On the contrary, specific force was reduced in animals treated with sActRIIB-Fc, in agreement with what has been already reported in hypertrophied muscle of myostatin-deficient mice (2,19,42). Third, we observed that sActRIIB-Fc treatment did not improve maximal tetanic force in vivo.…”
Section: Discussionsupporting
confidence: 92%
“…One of the major findings of the present study is that long-term disruption of ActRIIB signaling impairs mitochondrial function in skeletal muscle, which is comparable to data obtained in myostatin-deficient animals (2,6,19,45). We found actually that sActRIIB-Fc treatment dramatically reduced the maximal rate of oxidative ATP synthesis (Ϫ42%), which is considered a robust and highly reproducible in vivo index of oxidative mitochondrial capacity and has been widely used in research and clinical applications (4,7,26,32).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Indeed, beyond muscle hypertrophy, Mstn KO mice show a disturbed muscle function with loss of muscle strength and endurance in vivo or ex vivo accompanied with a decrease in mechanical performance, and ATP production during exercise [11,12,13,14]. In parallel, many other metabolic changes have been documented in Mstn KO muscle such as a decrease in mitochondrial content, disturbance in mitochondrial respiratory function with a decay in the respiratory control ratio in intermyofibrillar mitochondria, and a decline in porine activity [11,13,15].…”
Section: Introductionmentioning
confidence: 99%